2020
DOI: 10.1101/2020.04.25.061051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of fire intensity on plant growth forms in high-altitude Andean grassland

Abstract: 16Fires in the páramo grasslands of the tropical northern Andes vary in intensity at the 17 landscape scale. Fire suppression strategies, intended to conserve biodiversity and páramo 18 ecosystem integrity and function, could lead to the accumulation of high fuel loads and 19 ultimately fires of higher intensity. Yet the impact of fire intensity on páramos is not well 20 studied or understood. 5½ years after a fire, we measured plant growth form composition, 21 light transmission to the ground and soil tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Last but not least, extending the modeling approach implemented in this work to other key pressures (e.g., fire, Wu and Porinchu, 2019;Rivadeneira et al, 2020;Zomer and Ramsay, 2020) and plant groups (Luteyn, 1999) in the Páramo, as well as to other sky islands around the mountains of the world (Hoorn et al, 2018;Pausas et al, 2018;Nürk et al, 2019;Testolin et al, 2020), and more broadly to other island-like systems (Papadopoulou and Knowles, 2015;Lamichhaney et al, 2017;Cámara-Leret et al, 2020;Flantua et al, 2020), will help understanding climate change effects on unrelated taxa experiencing similar evolutionary processes (Condamine et al, 2018;Cortés et al, 2020;Nürk et al, 2020). Such systems offer natural experiments to assess the role of colonization and adaptation (Ding et al, 2020;McGee et al, 2020;Tito et al, 2020) in the past and ongoing responses to climate change, which undeniably will complement ecological predictive modeling.…”
Section: Perspectivesmentioning
confidence: 99%
“…Last but not least, extending the modeling approach implemented in this work to other key pressures (e.g., fire, Wu and Porinchu, 2019;Rivadeneira et al, 2020;Zomer and Ramsay, 2020) and plant groups (Luteyn, 1999) in the Páramo, as well as to other sky islands around the mountains of the world (Hoorn et al, 2018;Pausas et al, 2018;Nürk et al, 2019;Testolin et al, 2020), and more broadly to other island-like systems (Papadopoulou and Knowles, 2015;Lamichhaney et al, 2017;Cámara-Leret et al, 2020;Flantua et al, 2020), will help understanding climate change effects on unrelated taxa experiencing similar evolutionary processes (Condamine et al, 2018;Cortés et al, 2020;Nürk et al, 2020). Such systems offer natural experiments to assess the role of colonization and adaptation (Ding et al, 2020;McGee et al, 2020;Tito et al, 2020) in the past and ongoing responses to climate change, which undeniably will complement ecological predictive modeling.…”
Section: Perspectivesmentioning
confidence: 99%
“…Although the rapid inclusion of dead leaves in the first 2 y after fire contributes potential fuel to the next fire, it is the continued rise in tussock height that builds up much of the combustible material in later years. The presence of significant quantities of fuel not only increases the chances of fire spreading though the vegetation once it has started (Pels & Verweij 1992), it also increases the likelihood of a high-intensity fire, resulting in higher plant mortality and more damage to ecosystem services (Ramsay & Oxley 1996, Zomer & Ramsay 2020a). More frequent fires, with lower fuel loads, might be less damaging, and might even promote productivity (Hofstede et al 1995) and plant diversity (Bremer et al 2019, Keating 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Bremer et al (2019), Keating (2007) and Ramsay (2001) concluded that páramo vegetation recovery does not follow one particular successional trajectory. Fires can have very different effects on vegetation, depending on the intensity and extent of a particular fire (Luteyn, 1999; Sklenář & Ramsay, 2001; Suárez & Medina, 2001; Keating, 2007; Zomer & Ramsay, 2020). Fire behaviour is determined by the pre‐fire community structure (physical vegetation structure and fuel accumulation) and fire event conditions (Zomer & Ramsay, 2020).…”
Section: Introductionmentioning
confidence: 99%